Design of pipe diameter of polyester‐ramie nonwoven lining material for pipeline rehabilitation. Issue 4 (12th February 2020) - Fu, Lisong; Zhang, Shujie; Wang, Rui; Fang, Shu; Li, Danyang; Ma, Tianshuai; Zhao, Xuecheng
Abstract: In order to solve the problems of pipe diameter of polyester‐ramie nonwoven lining material used for sewage pipelines rehabilitation, the mathematical model of pipe diameter of lining material was established by using elastic mechanics method and composite piping design. The mixing ratio, the fiber web quantification and the needle‐punched density were selected to optimize the manufacturing process of polyester‐ramie nonwoven with thermal shrinkage rate and elongations at break, the results showed that the mixing ratio was 0.7, and the fiber web quantification was 600 g/m 2, and the needle‐punched density was 180 thron/cm 2 . Under this process, the thermal shrinkage rate is 8.72%, and the elongation at break is 83%, which is close to the theoretical value, indicating that the response surface method has practical application value. Combined with the mathematical model and the optimal condition of manufacturing process, the design extremum of pipe diameter of lining material for sewage pipelines with different pipe diameters is predicted, which provides the theoretical basis for the preparation of polyester‐ramie nonwoven composites for pipeline rehabilitation.